Enhancement of skills on drawing of free body diagrams with Tracker program - Pantian, Sarayut (Journal of Science and Technology CRRU, 2023)
The purposes of this research are to determine the effectiveness of the lesson plan and compare the average of the pre-and post-test scores of subjects who have been trained using the video by tracker program to teach physics in one-dimensional motion. Also focus on the process of drawing a free body diagram of the object to solve complex problems. The sample was used by purposive sampling consisted of 18 volunteer students from the Demonstration School of Thepsatri Rajabhat University, the 1st semester: 2023. Research tools included the lesson plan using tracker program in one-dimensional motion of an object. The results show that the effectiveness of the lesson plan is based on 80/80 criteria. It is found that the percentage of the average score, the score between the course (evaluation of experiments and exercises during the course) and after the course (learning result) is 88.33.and 82.61 respectively, and students have the ability to draw free body diagrams of post-test significantly higher than before study statistically 05.